Strengthening Disaster Management Discourse: An Evaluation of Disaster Education in Africa's Regional Platforms for Disaster Risk Reduction - Bang, Henry (African Journal of Education and Practice, 2023)
Purpose: Considering that the pedagogic space for disaster risk reduction (DRR) education is critical for enhanced resilience to disaster risks, this paper interrogates regional DRR education discourse in Africa. The focus is on the scope and depth to which DRR education has been mainstreamed into high-level regional meetings/platforms in the African continent. For this to be realised, first, the paper assesses whether the Africa Regional Platforms (ARPs) and high-level Ministerial Meetings for DRR perceive DRR education as a critical tool for mitigating disaster risks. Secondly, the paper gauges the depth to which identified determinants of DRR education have been integrated into the ARPs and High-Level Ministerial Meetings for DRR. Methodology: By utilising a post-positivist qualitative research approach, the paper has scrutinised primary data from all the ARPs and High-Level Ministerial Meetings for DRR spanning close to twenty-five years. All sourced documents were sorted, coded and thematically analysed. The coded categories captured the extent of DRR education discussed in the regional platforms/meetings, the number of determinants of DRR education discussed in the various platforms and the depth with which the determinants of DRR education were discussed. A Likert scale grading ranging from "Poor" as the lowest and "Excellent" as the highest was used to assess the enquiries and inform the findings. Findings: Through critical analysis and assessment, the findings have revealed the limited integration of DRR education during high-level DRR meetings in Africa. The analysis reveals an inconsistent and unsystematic DRR discourse during the Platforms/Meetings. Based on the Likert Scale grading, the two main enquiries of this research (scope of DRR education and the integration of DRR education determinants during the various Platforms) were both deemed to be "mediocre to fair". Although this assessment is subjective, it paints a good picture of the integration of DRR education into risk aversion discourses at the highest level in the African continent. Unique Contribution to Theory, Practice and Policy: This paper pioneers the first in-depth assessment of DRR education discourse at the highest regional level in Africa. It contributes by augmenting the literature on DRR education discourse and determinants of DRR education; provides DRR insights to educators, students and practitioners and has policy implications for the governance of disaster risks at the highest African regional level. Considering the pivotal role of education in strengthening resilience to disaster risks, the findings provide a compelling argument for mainstreaming DRR education into the ARPs and high-level Ministerial Meetings for DRR. Arguably, this would expedite DRR education uptake by African countries.